1973
DOI: 10.1111/j.1537-2995.1973.tb04476.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Study of Platelet Concentrates Stored at 22 C and 4 C

Abstract: Samples of platelet concentrate prepared by double plasmapheresis of volunteers were stored at 4 C and 22 C for four to ten days and cultured from 0072 hours on brain heart infusion media, thioglycolate broth, and tryptic soy broth and incubated at 22 and 37 C for 21 days. A closed system was used for 42 units and a limited entry system involving pooling of platelet concentrates was used for 68 units. All 110 units were negative for bacterial contamination at both 4 C and room temperature, based on cultures us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Barrett et al (1 992) found bacterial-derived adverse transfusion reactions more frequently in random platelet concentrates (0.1 4%) compared with apheresis concentrates (0.03%). Other investigators have described contamination rates at 0.3% (Mallin et al, 1973;Wren et al, 1974) to 2.4% depending on platelet concentrate shelf-life at the time of sampling (Buchholz et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrett et al (1 992) found bacterial-derived adverse transfusion reactions more frequently in random platelet concentrates (0.1 4%) compared with apheresis concentrates (0.03%). Other investigators have described contamination rates at 0.3% (Mallin et al, 1973;Wren et al, 1974) to 2.4% depending on platelet concentrate shelf-life at the time of sampling (Buchholz et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier reports a 2% blood contamination rate with staphylococcus spp. was recorded (Mollison et al, 1987). More recently contamination rates of 5-0.0001 YO have been reported (Puckett, 1988;Saxena et al, 1990;Goldman et al, 1991).…”
mentioning
confidence: 93%
“…Of the three measures, this one varies the most widely; it is susceptible to errors in aseptic technique, and the observation cannot be confirmed by comparing bacterial strains isolated from the blood component and that of the patient. Most often, these studies have focused on bacterial contamination of random donor platelet concentrates, with positive cultures ranging from 0 to 10% (6,7,22,23,31,48,72,125,154) and apheresis platelets ranging from 0 to 5% (2,29,83,133). In over 75% of "contaminated" platelet concentrates, fewer than 10 organisms per ml were detected (6,22,31).…”
Section: Measures Of Frequency Of Bacterial Contamination In Blood Prmentioning
confidence: 99%
“…Of the three measures, this one varies the most widely; it is susceptible to errors in aseptic technique, and the observation cannot be confirmed by comparing bacterial strains isolated from the blood component and that of the patient. Most often, these studies have focused on bacterial contamination of random donor platelet concentrates, with positive cultures ranging from 0 to 10% (6, 7, 22, 23, 31, 48, 72, 125, 154) and apheresis platelets ranging from 0 to 5% (2,29,83,133). In over 75% of "contaminated" platelet concentrates, fewer than 10 organisms per ml were detected (6,22,31).…”
Section: Introductionmentioning
confidence: 99%